Constraints on the growth of private policing: A comparative international analysis. (August 2019) - Singh, Anne-Marie; Light, Matthew
While much has been written on private security expansion in a few English-speaking industrialized democracies, less is known about why the industry does not develop uniformly around the world. We propose some hypotheses about constraints on private security growth in other settings, based on three comparative case studies in authoritarian states (Russia and Georgia), developing countries (Guyana and Trinidad) and non-'Anglosphere' industrialized democracies (continental Europe). In authoritarian states, private policing is more politically sensitive than in democratic states, sometimes resulting in more draconian restrictions on it. In developing societies, despite widespread fear of crime, potential consumers sometimes favour in-house measures over private security firms and electronic devices. In developed democracies, variation in private security growth reflects regulatory, institutional and ideological differences between the Anglosphere and continental Europe. We conclude that constraints on the private security industry's growth potential are more significant than many scholars have acknowledged.